2020
DOI: 10.1371/journal.pone.0232406
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of neonatal admissions and mortality at a regional and district hospital in the Upper West Region of Ghana; a cross sectional study

Abstract: Background High global neonatal deaths have triggered efforts to improve facility-based care. However, the outcomes achievable at different levels of care are unclear. This study compared morbidity and mortality patterns of newborns admitted to a regional and a district hospital in Ghana to determine outcome, risk and modifiable factors associated with mortality. Objective This study compared morbidity and mortality patterns of newborns admitted to a regional and a district hospital in Ghana to determine outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 50 publications
5
22
2
Order By: Relevance
“…Nigeria, and most of the patients were referred from other hospitals with complications on arrival. 31 The pattern and outcome of congenital malformations in their report was similar to that of our study with a preponderance of gastrointestinal malformations.…”
Section: Discussionsupporting
confidence: 87%
“…Nigeria, and most of the patients were referred from other hospitals with complications on arrival. 31 The pattern and outcome of congenital malformations in their report was similar to that of our study with a preponderance of gastrointestinal malformations.…”
Section: Discussionsupporting
confidence: 87%
“…Among neonatal factors, very low and low birth weights (54.4%) were found to be associated with overall clinically suspected sepsis in this study ( Table 2 ). Preterm birth and low birth weight were reported as associated risk factors of neonatal sepsis in previous studies as well [ 22 , 23 , 31 , 32 ]. However, others have found no association between neonatal sepsis and preterm birth or low birth weight [ 24 , 33 ].…”
Section: Discussionmentioning
confidence: 98%
“…This study describes the frequency of neonatal bacterial sepsis in two large tertiary care NICUs, which is one of the principal causes of hospitalization and mortality for neonates in developing countries [ 22 , 23 ]. We found the prevalence of bacteriologically confirmed neonatal sepsis (672/10,935, 6.1%) in the two study facilities to be lower than reports from Bangladesh (14.5%) [ 24 ] and Nepal (14%) [ 25 ], but similar to one from India (6.2%) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“… 13 Jaundice was one of the most common causes of neonatal mortality and responsive for 6.7% of neonatal death in Ghana. 14 In Ethiopia, of the total death at Ayder, about 98.3% occurred during the first week of their life 15 and at Aroresa in Sidama, neonatal mortality was 41 per 1000 live birth and neonatal complication was one of the predictors for neonatal mortality. 16 In the northwest part of Ethiopia, the study revealed that Jaundice was one of the significant predictors for neonatal mortality, especially under 7 days of age.…”
Section: Introductionmentioning
confidence: 99%